Association between nocturnal sleep duration and the risk of hyperuricemia among Chinese government employees: A cross-sectional study - An, Yanni; Li, Xuping; Ouyang, Feiyun; Xiao, Shuiyuan (Frontiers in Public Health, 2022)
Objectives: Evidence has shown that nocturnal sleep duration is associated with the risk of hyperuricemia, yet the findings are inconsistent. Thus, we aimed at exploring the association between nocturnal sleep duration and the risk of hyperuricemia in Chinese governmental employees. Methods: A total of 10,321 governmental employees aged 20 to 60 years were collected from the Chronic Disease Cohort Study of Governmental Employees in Hunan Province, China. Sleep duration was self-reported. And serum uric acid levels >420μmol/L in men and >360μmol/L in women were considered hyperuricemia. The association between nocturnal sleep duration and hyperuricemia risk was examined utilizing multivariate logistic regression models. To further examine the connection between nocturnal sleep duration and serum uric acid levels, multiple linear regression analyses were utilized. Results: The prevalence of hyperuricemia was 17.2%. The results of logistic regression demonstrated that, in contrast to participants whose sleep duration was 78 hours, those who slept for less than 7 hours had an elevated risk of hyperuricemia (OR=1.343, 95%CI: 1.126, 1.601). Further stratified analysis revealed that this association was still observed in those without obesity (OR=1.365; 95%CI: 1.127, 1.655), hypertension (OR=1.290, 95%CI: 1.054, 1.578), or diabetes mellitus (OR=1.361, 95%CI: 1.136, 1.631). Multiple linear regression showed that shorter sleep duration (< 7 hours) was positively correlated with serum uric acid levels. In comparison to individuals who slept for 78 hours, those with sleep duration of fewer than 7 hours had serum uric acid levels that were 7.231 μmol/L (95% CI: 2.875, 11.588) higher. Conclusion: Short nocturnal sleep duration (< 7 hours) was associated with a higher risk of hyperuricemia, especially in participants without obesity, hypertension, or diabetes mellitus. Besides, short nocturnal sleep duration was related to greater uric acid levels.